"Corruption premium" on municipal borrowing cost: the case of Spanish Mayors. Issue 3 (2nd September 2019) - Bastida, Francisco; Guillamón, María-Dolores; Benito, Bernardino; Ríos, Ana-María
Abstract : Purpose: The purpose of this paper is to examine the impact of mayors' corruption on the municipal interest rate set by lenders. Design/methodology/approach: The sample consists of a panel data for all the Spanish cities with population over 50, 000 for 2002–2013 (130 municipalities). In line with previous literature and the structure of the panel data, the authors use a generalized method of moments equation to the main model and three robustness checks. Findings: The results, robust to different specifications, indicate that banks do not take mayors' corruption as a significant risk component of the municipal solvency. The data show a "corruption premium" ranging from −1 to 33 basis points, which aligns with the size of the "corruption premium" found by the literature, but the significance is low. This finding is connected, on the one hand, with the rigid, thorough Spanish legal framework ruling municipal financial management, and on the other hand, with the characteristics of mayors' corruption. Robust evidence shows that key financial indicators influence interest rates: current saving, with a strong influence, and level of indebtedness, to a lesser extent. Besides, more populated cities pay lower interest rates. Research limitations/implications: The main limitation stems from the calculation of interest rate, because but sharp debt changes may decrease the accuracy. Practical implications: The data prove that banks value this surplus as a sign of solvency and set lower interest rates. Considering that this financial indicator is key for setting the interest rate, as a point for practitioners, current saving should be monitored by the municipal financial officer, as a way to reduce the financial cost. Besides, legislation should consider current saving as a benchmark to set balanced budget rules or to establish conditions for municipalities to get into greater indebtedness. Originality/value: This is the first research on municipal interest rate premium due to corruption in Spain.